Overcoming neoliberal globalization: social-ecological transformation from a Polanyian perspective and beyond - Brand, Ulrich; Görg, Christoph; Wissen, Markus (Globalizations, 2020)
The ecological crisis has intensified in many respects. Prominent proposals to deal with the crisis are discussed under the header 'sustainability transformations' or even 'Great Transformation'. We argue that most contributions suffer from a narrow analytical approach to transformation ignoring the largely unsustainable dynamics of global capitalism and the power relations involved in it. Thus, a 'new critical orthodoxy' of knowledge about transformation is emerging which runs the danger to contribute to a spatially and socially highly uneven green capitalism. This article claims that the current debate on social-ecological transformation can be enriched by a Polanyian understanding but also based on regulation theory. We distinguish between three types of transformation: incremental adaptation of the current institutional systems, institutional change in favour of a new 'green' phase of capitalism, and a post-capitalist great transformation that implies a profound structural change of the mode of production and living.
Keywords: POLANYI, Karl, 1886-1964; capitalism; crises; debates & debating; ecological crisis; globalization; imperial mode of living; nature as fictitious commodity; regulation theory; social ecology; social-ecological transformation; sustainability